Class Ceramics: Tuneable Nanostructuring of Highly Transparent Zinc Gallogermanate Glasses and Glass‐Ceramics (Advanced Optical Materials 4/2014). Issue 4 (April 2014) - Chenu, Sébastien; Véron, Emmanuel; Genevois, Cécile; Matzen, Guy; Cardinal, Thierry; Etienne, Auriane; Massiot, Dominique; Allix, Mathieu
<x xml:space="preserve">Abstract</x> Highly transparent nanostructured gallogermanatebased glass and glass‐ceramic materials are reported on page 364 by M. Allix and co‐workers. These materials present nanoscale phase separations, whose size can be tailored depending on the nominal composition. The large variety of accessible compositions combined with precise control of the nanostructure offer a great opportunity to design new highly transparent nanostructured materials with a wide range of tuneable optical properties both in the visible and the infrared ranges. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>